Comparison of ease of intubation in sniffing position and further neck flexion - Kiran Kumar Gudivada; Nirmala Jonnavithula; Sai Lakshman Pasupuleti; Chaitanya Prathyusha Apparasu; Syama Sundar Ayya; Gopinath Ramachandran (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Optimization of patient's head and neck position for the best laryngeal view is the most important step before laryngoscopy and intubation. The objective of this prospective crossover study was to determine the differences, if any, between the gold standard sniffing position (SP) and the further head elevation (HE) (neck flexion) with regard to the incidence of difficult laryngoscopy, intubation difficulty, and variables of the I ntubation Difficulty Scale (IDS) in adult patients undergoing elective surgery under general anesthesia. Material and Methods: In the "SP" the neck must be flexed on the chest by elevating the head with a cushion under the occiput and extending the head at the atlanto-occipital joint. Our study was carried out to evaluate the glottic view in SP compared to further HE by 1.5 inches during direct laryngoscopy in elective surgeries. Patients were randomly assigned to either Group A ("SP" during first laryngoscopy and "HE" during second laryngoscopy) or vice versa in Group B. The effect of patient position on ease of intubation was assessed using a quantitative scale - The intubation difficulty scale (IDS). Results: There were significant differences with regard to glottic visualization (P = 0.00), number of operators (P = 0.001), laryngeal pressure (P = 0.00), and lifting force (P = 0.00) required for intubation and IDS (P = 0.00), thus favoring further HE position. Conclusion: We conclude that the HE position is superior to standard SP with regard to ease of intubation as assessed by IDS.